Institutional Ownership, Firm Size, Leverage, and Profitability: The Impact on Firm Value in the Indonesian Banking Sector - Irawan, Syahril; Nugroho, Lucky (Business, Management & Accounting Journal (BISMA), 2025)
This study aims to examine the effect of institutional ownership, company size, leverage, profitability on firm value. The population in this study is a banking sub-sector company listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The sampling technique used in this study was purposive sampling method, resulting in a sample of 42 companies over a period of 5 years, with a total of 210 data samples that met the criteria. The sampling method uses purposive sampling method. The data used in this study are secondary data obtained from the official website of the Indonesia Stock Exchange (IDX) and the official website of each company. The data analysis method used is multiple linear regression analysis with the help of the IBM SPSS 25 application. The results showed that institutional ownership, company size, and profitability have no significant effect on firm value. In contrast, leverage has a negative influence on firm value. These findings provide insight for company management and investors regarding the factors that influence firm value in the banking sub-sector.